¿ES ESPAÑA UN ESTADO CASIFEDERAL EN POLÍTICA CULTURAL? ARTICULACIÓN Y CONFLICTO ENTRE LA POLÍTICA CULTURAL DEL ESTADO CENTRAL Y LA DEL GOBIERNO DE CATALUÑA - Mariano Martín Zamorano (Revista d'Estudis Autonòmics i Federals, 2014)
Right back from the 1970, comparative policy analyses have been emphasizing how cultural policy has moved towards models administratively decentralized and respectful with cultural plurality. Spain, often characterized as a widely decentralized country, has also been defined as a country of rich cultural and linguistic diversity. Its institutional structure, halfway between centralist and federal political system, has also been described as a quasi-federal system. However, from the cultural policy sector, can be said that Spain is a quasi-federal political system? In this article we argue that, despite the broadly decentralized management of cultural policies, Central Government’s most recent legal and organizational processes are far from developing a plurinational federal system and are actually growingly oriented towards recentralization and symmetrisation.